Peran Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SD Islam Modern Darunnajah Serang - nadya nadziratul ula; Andriani Sariwardani; Mutoharoh Mutoharoh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Leadership is the attitude and behavior to influence subordinates so that they can work together, forming a harmonious cooperation with considerations of efficiency and effectiveness to achieve the work productivity targets that have been set. This study aims to analyze the role of school principal leadership style in improving teacher performance at SD Islam Modern Darunnajah Serang. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with the principal, teachers, and administrative staff, as well as direct observation. The results indicate that the leadership style applied by the principal, particularly transformational and participative leadership styles, has a significant impact on improving teacher performance. These leadership styles foster increased motivation, commitment, and job satisfaction among teachers, which ultimately contributes to the improvement of the quality of teaching. Additionally, good communication and the provision of rewards to teachers also serve as supporting factors in enhancing their performance. Keywords: leadership style, school principal, teacher performance, SD Islam Modern Darunnajah Serang, educational quality improvement.